Marcadores inflamatórios, maturação oocitária e desenvolvimento embrionário inicial em bovinos - Alvarado Rincón, Joao Alveiro (2019)
The inflammatory response arises as a mechanism of the immune system to fight infectious agents. Studies suggest an association between inflammation and fertility, mainly due to the modulation and synthesis of inflammatory mediators. High-density lipoprotein (HDL) is the main lipoprotein in follicular fluid. It has anti-inflammatory and antioxidant properties, mainly derived from its lipid composition, apolipoprotein AI (ApoAI) and paraoxonase-1 (PON1). On the other hand, lipopolysaccharides (LPS) are bacterial endotoxins that act as potent stimulator of the inflammatory response. The objective of this study was to evaluate the effect of HDL during in vitro maturation (IVM) on oocyte maturation and early embryonic development and to evaluate the effect of bovine oocyte exposure to LPS in vitro and in vivo on oocyte maturation and embryonic development in cattle. In the first study, cumulus oocyte complex (COCs) were supplemented with HDL protein during IVM, after, were fertilized (IVF) and cultured in vitro (IVC). In the second study, COCs were challenged with LPS during IVM and after, underwent IVF and IVC. Separately, COCs were subjected to IVM without LPS, thereafter they underwent IVF and during the 7 days of IVC they were challenged with LPS. Still in the second study, heifers were challenged with intravenous LPS during follicular wave synchronization. The animals were slaughtered, the ovaries were collected and COC recovery was performed. All recovered COCs underwent IVM, IVF, and IVC. In this way, we found that the addition of the HDL/ApoAI complex of human plasma during IVM, in the absence of PON1 activity, decreases the initial embryonic development. Furthermore, the exposure of bovine oocytes to LPS during IVM decreases the nuclear maturation rate, however, it was not able to affect the initial embryonic development. Similarly, exposure of zygotes to LPS during IVC did not affect embryonic development. However, infusion of LPS into heifers decreased the rate of cleavage, but the embryonic development was similar to that of the non-LPS challenged group. It is concluded that the interaction of HDL-ApoAI-PON1 complex components may affect bovine fertility at oocyte level and subsequent embryonic development. In the same way, the LPS can affect the oocyte and embryonic development; however, the mechanisms by which this happens appear to be different in vitro and in vivo.